2010
DOI: 10.1590/s1516-44462010005000005
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of relapse in the second follow-up year post cognitive-behavior therapy for panic disorder

Abstract: OBJECTIVE: To investigate predictors of relapse two years after a brief cognitive-behavior group therapy in patients with panic disorder who had failed to respond to pharmacologic treatment. METHOD: A total of 56 patients with panic disorder were followed who had met remission criteria at 1 year evaluation after 12 sessions of cognitive-behavior group therapy. Demographic and clinical features and life stressors were investigated as predictors of relapse. RESULTS: At the 2 year assessment, 39 (70%) patients ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
0
19
1
2
Order By: Relevance
“…Previous studies have identified a number of risk factors for recurrence, including demographic and socioeconomic characteristics (younger age, female sex, and lower household annual income), stressful life events (financial crisis, interpersonal conflict, etc. ), tobacco use, psychological disorders (including major depression and generalized anxiety disorder), personality disorders, panic symptoms during episodes, family history, and childhood traumatic experiences . Identification of these risk factors has laid a strong foundation for early identification and prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified a number of risk factors for recurrence, including demographic and socioeconomic characteristics (younger age, female sex, and lower household annual income), stressful life events (financial crisis, interpersonal conflict, etc. ), tobacco use, psychological disorders (including major depression and generalized anxiety disorder), personality disorders, panic symptoms during episodes, family history, and childhood traumatic experiences . Identification of these risk factors has laid a strong foundation for early identification and prevention.…”
Section: Introductionmentioning
confidence: 99%
“…(2) can be provided by non-physicians (e.g. trained psychologists or nurses); (3) are associated with lower relapse rates; and (4) appear to be more cost -effective in the long run (Heldt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Entre os preditores de pior resposta ao tratamento, os estudos relatam a presença de comorbidades com o TP, como a fobia social e o estresse pós-traumático (Chavira et al, 2009), a distimia e a ansiedade generalizada (Heldt et al, 2006). Também a sensibilidade à ansiedade após tratamento farmacológico combinado com TCC individual (Chavira et al, 2009) e os eventos estressores negativos no período de dois anos após TCCG foram preditores de pior resposta ao tratamento (Heldt et al, 2011).…”
unclassified